Peran Pendidikan Keuangan dan Pengaruhnya Terhadap Literasi Keuangan pada Siswa SMA PGRI 4 Jakarta - Ari Wahyu Leksono; Dwi Narsih (Peneliti.net, 2020)
Financial education is considered one of the solutions to overcome the problem of low financial literacy. Through this view, this study wants to find out whether financial education can really affect financial literacy in high school students PGRI 4 Jakarta. This research is quantitative with associative type. The population in this study were all students of SMA PGRI 4 2018 Academic Year as many as 497 students. The sample of the study was 205 students with a sample technique that is stratified sampling. Data collection techniques using questionnaires and instruments tested the validity and reliability testing. Data analysis techniques using linear regression test. The results showed that there was no significant effect of financial education on financial literacy in SMA PGRI 4 Jakarta students.